Obstacles to diagnosis and treatment of Lyme disease in the USA: a qualitative study. Issue 6 (11th June 2018) - Hirsch, Annemarie G; Herman, Rachel J; Rebman, Alison; Moon, Katherine A; Aucott, John; Heaney, Christopher; Schwartz, Brian S
Abstract : Objective: For many individuals with Lyme disease, prompt treatment leads to rapid resolution of infection. However, severe complications can occur if treatment is delayed. Our objective was to identify themes around belated diagnosis or treatment of Lyme disease using the General Model of Total Patient Delay (GMTPD). Design: We conducted a qualitative interview study using indepth telephone interviews. Setting: Participants were patients from a large, integrated health system in the state of Pennsylvania, USA. Participants: There were 26 participants. Participants had to have a diagnosis of Lyme disease between 2014 and 2017 and a positive IgG western blot. We used a stratified purposeful sampling design to identify patients with and without late Lyme disease manifestations. To ensure variation in care experiences, we oversampled patients diagnosed outside of primary care. Outcome measures: We asked participants about their experience from first Lyme disease symptoms to treatment. We applied an iterative coding process to identify key themes and then synthesised codes into higher order codes representing the GMTPD stages: appraisal delay (symptom to recognition of illness); illness delay (inferring illness to deciding to seek help); behavioural delay (deciding to seek help to the act of seeking help); scheduling delay (seeking help to attending an appointment); and treatment delay (attending appointment to treatment). Results: Appraisal delay themes included symptom misattribution, intermittent symptoms and misperceptions about the necessity of a bull's-eye rash. Health insurance status was a driver of illness and behavioural delays. Scheduling delay was not noted by participants, in part, because 10 of the 26 patients went to urgent care or emergency department settings. Misdiagnoses were more common in these settings, contributing to treatment delay. Conclusion: Our study identified potentially modifiable risk factors for belated treatment. Targeting these risk factors may minimise time to treatment and reduce the occurrence of preventable complications.